Development of a simulated round of golf - Hayes, P. R.; van Paridon, K.; French, D. N.; Thomas, K.; Gordon, D. A. (International Journal of Sports Physiology and Performance, 2009)
Purpose: The aim of this study was to develop a laboratory-based treadmill simulation of the on-course physiological demands of an 18-hole round of golf and to identify the underlying physiological responses. Methods: Eight amateur golfers completed a round of golf during which heart rate (HR), steps taken, and global positioning system (GPS) data were assessed. The GPS data were used to create a simulated discontinuous round on a treadmill. Steps taken and HR were recorded during the simulated round. Results: During the on-course round, players covered a mean (±SD) of 8,251 ± 450 m, taking 12,766 ± 1,530 steps. The mean exercise intensity during the on-course round was 31.4 ± 9.3% of age-predicted heart rate reserve (%HRR) or 55.6 ± 4.4% of age-predicted maximum HR (%HRmax). There were no significant differences between the simulated round and the on-course round for %HRR (P = .537) or %HR max (P = .561) over the entire round or for each individual hole. Furthermore, there were no significant differences between the two rounds for steps taken. Typical error values for steps taken, HR, %HRmax, and %HRR were 1,083 steps, ±7.6 b·min-1, ±4.5%, and ±8.1%, respectively. Conclusion: Overall, the simulated round of golf successfully recreated the demands of an on-course round. This simulated round could be used as a research tool to assess the extent of fatigue during a round of golf or the impact of various interventions on golfers.